Identification of a new HLA-A2-restricted T-cell epitope within HM1.24 as immunotherapy target for multiple myeloma - Hundemer, Michael; Schmidt, Stefanie; Condomines, Maud; Lupu, Alaviana; Hose, Dirk; Moos, Marion; Cremer, Friedrich Walter; Kleist, Christian; Terness, Peter; Belle, Sebastian; Ho, Anthony Dick; Goldschmidt, Hartmut; et al. (Experimental hematology, 2006)
Objective - The aim of this study was identification of human leukocyte antigen (HLA)-A2-restricted T-cell epitopes within the HM1.24 antigen as target for multiple myeloma (MM)-directed specific peptide-based immunotherapy. - Methods - The HM1.24 sequence was scanned for immunogenic peptides using the HLA-binding prediction software SYFPEITHI and BIMAS. Peripheral blood mononuclear cells from HLA-A2+ healthy volunteers/blood donors (ND) were stimulated with autologous HM1.24-peptide-loaded dendritic cells, and expanded in vitro. Activation of T cells was assessed by ELISpot and cytotoxicity by 51Chromium (51Cr)-release assays. T2-cells pulsed with irrelevant peptide, the HM1.24−/HLA-A2+ breast carcinoma cell line MCF-7 and the HM1.24+/HLA-A2− myeloma cell line RPMI-8226 were used as controls. Expression of the HM1.24 gene (BST2) was assessed using purified plasma cells and Affymetrix-U133A+B microarrays. Frequency of peptide-specific CD8+ T cells was detected using the flow-cytometric tetramer technique. - Results - Of eight nona-peptides with the highest probability of binding to HLA-A2, the HM1.24 aa22-30 peptide (LLLGIGILV) showed the most frequent activation of CD8+ T cells in healthy volunteers (specific activation in 8 of 11 [73%] ND; compared with 5-19% for the 7 other HM1.24 peptides). Antigen recognition by the HM1.24 aa22-30-specific CD8+ T cells was HLA-A2-restricted (ELISpot with HLA-A2-blocking antibodies: median, 15; range, 14-18 spots/well; isotype-control antibodies: median, 47; range, 44-48). HM1.24-aa22-30-specific CD8+ T cells lysed HLA-A2+ myeloma-derived cell lines (51Cr-release assay: XG-1 vs MCF-7, 91% vs 0%; U266 vs MCF-7, 38% vs 4.2%; IM-9 vs RPMI-8226, 22% vs 0%). Using the cross-reactive Neisseria meningitidis peptide LLSLGIGILV-specific CD8+ T cells recognizing target cells loaded with the HM1.24 aa22-30 peptide (LLLGIGILV) as well as the myeloma-derived cell line U266 could be expanded from MM patients. The HM1.24 gene was expressed at comparable levels by plasma cells from 65 MM patients, 7 patients with monoclonal gammopathy of undetermined significance, and 7 ND. - Conclusions - HM1.24 aa22-30 is a newly identified HLA-A2-restricted T-cell epitope that is processed and presented by major histocompatibility complex class I. Specifically activated CD8+ T cells are able to lyse MM cell lines. We conclude that HM1.24 aa22-30 represents a suitable candidate target for a specific peptide-based immunotherapy of MM.